2015
DOI: 10.1111/jocn.12846
|View full text |Cite
|
Sign up to set email alerts
|

The changing boundaries of nursing: a qualitative study of the transition to a new nursing care delivery model

Abstract: This study highlights the challenges in relation to the introduction of new nursing care delivery models within hospital settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 27 publications
(49 reference statements)
0
19
0
Order By: Relevance
“…To ensure that this will continue on the longer term, we recommend appointing (a group of) professionals working in the organization who are responsible for a structural embedding of physical activities into rehabilitation. In this way, "local ownership" is created, which has been previously shown to contribute positively to successful sustainability (31,33,37,38).…”
Section: Discussionmentioning
confidence: 99%
“…To ensure that this will continue on the longer term, we recommend appointing (a group of) professionals working in the organization who are responsible for a structural embedding of physical activities into rehabilitation. In this way, "local ownership" is created, which has been previously shown to contribute positively to successful sustainability (31,33,37,38).…”
Section: Discussionmentioning
confidence: 99%
“…In the new model, nurses must draw on higher levels of critical thinking as they provide care to patients and monitor them without caregivers' assistance. Rhéaume et al () reported that nurses had to find a different way of knowing patients in the new nursing care delivery model. Critical thinking is an essential skill for providing safe nursing care and maintaining nursing competence (Hoffman, ); it ensures patient safety and quality of care by improving nursing performance (Fero, Witsberger, Wesmiller, Zullo, & Hoffman, ).…”
Section: Introductionmentioning
confidence: 99%
“…Is it possible for nurses to develop their knowledge patterns under these unstable working conditions? Focusing on cost‐effectiveness can distort the aim of individualized and holistic nursing care attention (Rhéaume et al, ). In fact, research in Europe suggested that the increase in the workload of nurses increases the probability of hospital deaths and significantly decreases patient care quality (Aiken et al, ).…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…New precarious work conditions can unfavorably affect care relationships, mainly because of two important matters: a) stress and vulnerability affect nurses mentally and physically; and b) adverse work conditions, such as increased workload and shifting, negatively impact not only care relationships but also space for teaching. Restrictions and cost control can overrate strictly physical techniques and perspectives of care above other functions whose results are less tangible (Rhéaume et al, ). These conditions can affect the construction of empiric, ethical, aesthetic, and personal knowledge.…”
Section: Discussion Of Findingsmentioning
confidence: 99%